PENGARUH MANAJEMEN LABA TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE PADA PERUSAHAAN YANG MELAKUKAN MANIPULASI AKRUAL DAN MANIPULASI REAL (Pada Perusahaan Pertambangan Yang Telah Terdaftar Di Bursa Efek Indonesia (BEI) Pada Tahun 2017-2019) - Era Perdana; Dwiyani Sudaryanti; Maslichah Maslichah (Universitas Islam Malang, 2021)
This study aims to determine the differences in earnings management on the Corporate Social Responsibility Disclosure: Testing of Accrual Manipulation and Real Manipulation (in mining companies that have been listed on the Indonesia Stock Exchange (IDX) in 2017-2019). Based on the calculation data, there are 25 companies that selected to be the sample. The results of the analysis. Based on the calculation of the F test or testing simultaneously, it shows that Accrual Profit Manipulation and Real Profit Manipulation simultaneously affect Corporate Social Responsibility. Based on the calculation of the partial test, it shows that the results of the Accrual Profit Manipulation and Real Profit Manipulation variables have a significant value less than 0.05, which means that Accrual Profit Manipulation and Real Profit Manipulation have an effect on Corporate Social Responsibility.Keywords: accrual manipulation, real manipulation, Corporate social responsibility